3D cellular architecture modulates tyrosine kinase activity, thereby switching CD95-mediated apoptosis to survival - Gülcüler Balta, Gülce Sıla; Kleber, Susanne; Beaudouin, Joël; Balta, Emre; Chen, Si; Samstag, Yvonne; Tanaka, Motomu; Martín-Villalba, Ana (Cell reports, 2019)
The death receptor CD95 is expressed in every cancer cell, thus providing a promising tool to target cancer. Activation of CD95 can, however, lead to apoptosis or proliferation. Yet the molecular determinants of CD95’s mode of action remain unclear. Here, we identify an optimal distance between CD95Ligand molecules that enables specific clustering of receptor-ligand pairs, leading to efficient CD95 activation. Surprisingly, efficient CD95 activation leads to apoptosis in cancer cells in vitro and increased tumor growth in vivo. We show that allowing a 3D aggregation of cancer cells in vitro switches the apoptotic response to proliferation. Indeed, we demonstrate that the absence or presence of cell-cell contacts dictates the cell response to CD95. Cell contacts increase global levels of phosphorylated tyrosines, including CD95’s tyrosine. A tyrosine-to-alanine CD95 mutant blocks proliferation in cells in contact. Our study sheds light into the regulatory mechanism of CD95 activation that can be further explored for anti-cancer therapies.
Gesehen am 13.02.2020